Tingkat Pemahaman Keselamatan Dan Kesehatan Kerja Pada Pembangunan Gedung MAN 2 Banggai Standar ISO 45001 - Syamsu Basiri; Ahmad; Mukhtar Lutfie (Jurnal Karajata Engineering, 2025)
Occupational Safety and Health is crucial in construction to protect workers and prevent accidents. However, in projects such as the MAN 2 Banggai Building, OHS implementation, particularly in first aid and near miss incidents, remains inadequate. The increasing number of occupational fatalities in Central Sulawesi highlights the urgent need to improve the OHS evaluation system in the field. To address this challenge, this study uses the Countenance Stake Model linked to the ISO 45001 standard. The purpose of this study was to evaluate the extent of workers' understanding of OHS principles, assess strengths and weaknesses in their implementation, and provide data-based recommendations for improvement. The evaluation results indicate that although workers are quite strong in risk identification, there are weaknesses in OHS policies and worker technical competencies. While resources and communication are adequate, aspects of documentation, internal audits, and management reviews still need to be improved. Organizations should raise worker awareness through regular evaluations and targeted training.